2020
DOI: 10.4103/jfmpc.jfmpc_491_20
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle behavior of budding health care professionals: A cross-sectional descriptive study

Abstract: Background: College life is a crucial period and at this age, students are more likely to get involved in unhealthy lifestyle behavior like poor dietary habits, physical inactivity, and use of substances, etc. Objectives: Study objectives were to determine the lifestyle behavior of budding healthcare professions and to determine the association of bio-physical profiles with their personal profile, activity, sleep, and dietary pattern. Settings and Design:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
2
8
0
3
Order By: Relevance
“…Si bien se encuentra en la literatura que la información es necesaria, pero no suficiente, para lograr cambios en el comportamiento, sí se requiere como primer paso en el establecimiento de comportamientos preventivos (Guerra, Aldana y Rojas, 2020). Lo anterior es relevante si se considera la necesidad de congruencia entre lo que hace el profesional y lo que transmite (Sharma et al, 2020), por lo cual no basta que los futuros profesionales de Psicología sepan qué es el VIH, sino que al mismo tiempo tengan una conducta sexual segura, por lo que en esta investigación se buscó analizar sus creencias y el uso del condón en relaciones sexuales en los estudiantes.…”
Section: Principales Palabras Otorgadas Por Los Estudiantes De Psicol...unclassified
See 2 more Smart Citations
“…Si bien se encuentra en la literatura que la información es necesaria, pero no suficiente, para lograr cambios en el comportamiento, sí se requiere como primer paso en el establecimiento de comportamientos preventivos (Guerra, Aldana y Rojas, 2020). Lo anterior es relevante si se considera la necesidad de congruencia entre lo que hace el profesional y lo que transmite (Sharma et al, 2020), por lo cual no basta que los futuros profesionales de Psicología sepan qué es el VIH, sino que al mismo tiempo tengan una conducta sexual segura, por lo que en esta investigación se buscó analizar sus creencias y el uso del condón en relaciones sexuales en los estudiantes.…”
Section: Principales Palabras Otorgadas Por Los Estudiantes De Psicol...unclassified
“…Lo anterior se torna relevante en los estudiantes de Psicología por dos motivos: 1) porque es necesario diseñar estrategias de intervención para promover el uso del condón en relaciones sexuales, ya que al menos en la muestra evaluada se observa que tienen conductas de riesgo que los puede hacer susceptibles de infección por VIH (Novales-Castro et al, 2019), y 2) de acuerdo con Sharma et al (2020), es indispensable que como profesionales de la salud se adopten estilos de vida saludables acordes con lo que se desea promover; en este sentido, no basta con que los estudiantes de Psicología estén formados y capacitados en la prevención o tratamiento del VIH, sino que además tengan conductas sexuales preventivas, creencias positivas hacia el uso del condón, así como una actitud favorable hacia el trabajo profesional con personas con diagnóstico de VIH.…”
Section: Principales Palabras Otorgadas Por Los Estudiantes De Psicol...unclassified
See 1 more Smart Citation
“…1 As per World Health Organization (WHO) report, approximately 60% of contributing factors to health and quality of life of individuals are concerned with lifestyle practices. 2 Healthy lifestyle is a way that includes physical activity, balanced diet, stress management and avoidance of substances use. 3 The incidences of some non communicable diseases like hypertension, obesity, diabetes mellitus, and cardiovascular diseases have been rising in the country since few decades due to the unhealthy lifestyle of the people.…”
Section: Introductionmentioning
confidence: 99%
“…I came across a study published in JFMPC in July 2020, which was conducted on budding healthcare professionals regarding their lifestyle behaviours. [ 1 ] The authors reported that a significant number of professionals engaged in unhealthy lifestyle behaviours. It was recommended that future research should focus on potential promoters to adopt healthy lifestyle behaviours at medical universities.…”
mentioning
confidence: 99%